Modeling of a Railway Sanding System Using Vibration Fluidization - Bulavin Y.P. (EDP Sciences, 2021)
The model of the sand distributor of the sand feeding system of traction rolling stock, the operation of which is based on the effect of vibration fluidization of sand, has been considered. A pneumatic pulsator was used as a source of vibration impact. Experimental studies have shown that this design allows for a continuous regulated supply of sand. The power of the sand distributor membrane vibrations at the disturbing frequency can be used as a criterion characterizing the impact of the pulsator on the sand. There is a close to linear dependence of the sand flow rate on the power of vibrations.